Challenges of the metaverse in the learning processes of teachers in the classroom - Lozano-Ramirez, Ma. Cruz (2024)
Introduction. The metaverse is a construction of universes operated in digital environments where users connect to alternate realities on an identity platform through avatars that reflect their appearance, physical movements, body and facial expressions. Objective. To identify teachers’ knowledge about the metaverse and propose pedagogical strategies that support its incorporation into the thematic content of the subjects. Method. 68 teachers working in higher education institutions between 36 and 55 years of age participated. A non-parametric test (Chi-Square) was applied to identify possible relationships between the variable Knowledge of the Metaverse and the activities of teachers on technological trends, adaptation and learning dynamics on artificial intelligence of students. Results. It was identified that only 46 % of the teaching staff knows what the Metaverse is and that non-parametric tests report an association between knowledge of the Metaverse and the updating of the teaching staff in technological trends and the learning dynamics of the students in the units. Discussion. The incorporation of pedagogical strategies with immersive experiences in the contents of the subjects implies the investment in technological infrastructure, the redesign of contents, virtual environments, redefinition of roles (teachers - students). It is taking the physical classroom to a virtual environment. These processes must necessarily begin with the diagnosis of the technological infrastructure and the updating needs of the teaching staff in order to, in a second stage, continue with the implementation of actions and in a third stage, evaluate their impact.